10.1016/s1558-0164(09)70146-4 (CrossRef Listing of Deleted DOIs, 2000)
Background Parasitism is widespread in Neotropical reptiles, yet hematologic variation remains poorly characterized for many species. The Black Spiny-tailed Iguana (Ctenosaura similis) commonly harbors both intracellular hemoparasites and ticks, but population-based hematologic data under natural field conditions are limited. Objectives To characterize population-level hematologic values using descriptive hematologic intervals in free-ranging adult C. similis, and to evaluate associations between hematologic variables, intracellular hemoparasites, and tick burden. Methods Blood samples were obtained from 89 free-ranging adult iguanas from two sites in Costa Rica. Hemoparasites were identified based on blood smear morphology. Ticks were removed from each animal, then counted and categorized by life stage. Hematologic variables included erythrogram, white blood cell (WBC) counts, thrombocyte counts, and total solids. Descriptive hematologic intervals were calculated using the robust method. Associations between parasitism and hematologic variables were evaluated using linear and multiple regression models. Results Hemoparasite prevalence was high (93.3%), but hemoparasite loads were not significantly associated with erythrogram or WBC variables. In contrast, tick burden was associated with several factors. Hemoglobin concentration decreased with increasing numbers of adult ticks. Adult female ticks remained negatively associated with hemoglobin in adjusted models. WBC showed stage-specific relationships: heterophil-to-lymphocyte ratios increased with nymph abundance, and eosinophil counts increased with adult female ticks. All significant models had low explanatory power (R 2 ≤ 0.14). Conclusions Tick burden, but not hemoparasite load, was associated with variation in hematologic variables in C. similis. These findings provide population-based hematologic context for this species and support cautious interpretation of hematologic data in parasitized reptiles.